Penguatan Pendidikan Karakter pada Generasi Muda Melalui Personifikasi Karakter Pandawa dalam Wayang Kulit - Sukirno Hadi Raharjo Sukirno; Siti Utami Dewi Ningrum (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
The main problem discussed in this research is the negative impact of modernization which has the potential to damage the character of Indonesia's young generation. This research aims to explore the potential for character education through the application of Pandawa character personification in the traditional art of Wayang kulit. The method used is descriptive qualitative, by analyzing the representation of the Pandawa characters in Shadow Puppets and the values ​​contained therein. Research findings show that Wayang kulit not only maintains local wisdom values, but also carries moral messages and character values ​​that can be adopted by the younger generation. The personification of the Pandawa character highlights positive traits such as courage, loyalty and leadership, which are relevant to character education. The conclusion of this research is that Shadow Puppetry can be an effective tool for strengthening the character of the younger generation, while maintaining Indonesia's cultural heritage. The application of the results of this research can be the basis for developing a culture-based character education program, which is expected to produce a young generation who are responsible and have noble values.